2017
DOI: 10.1108/ijcma-01-2016-0003
|View full text |Cite
|
Sign up to set email alerts
|

Conflict and creativity in inter-organizational teams

Abstract: Purpose This paper aims to examine the effects of task and relationship conflicts on team creativity, and the moderating role of shared leadership in inter-organizational teams. An inter-organizational team normally comprises employees from collaborated organizations brought together to conduct an initiative, such as product development. Practitioners and researchers have witnessed the prevalence of conflict in inter-organizational teams. Despite significant scholarly investigation into the importance of confl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 138 publications
(225 reference statements)
7
79
0
2
Order By: Relevance
“…We choose employee innovative behavior as an outcome variable because, as innovation has been widely regarded as an important source of an organization's competitive advantage, it is essential to identify factors that increase team innovation performance (Shin et al, 2017). Scholars have increasingly suggested that conflict is an important perspective for studies on innovation (Hu et al, 2017). Previous studies on how conflict affected team innovation generated mixed results: some indicated that cognitive conflict could promote team innovation (Lu et al, 2011), whereas others proposed that both cognitive and affective conflicts negatively related to innovation (He et al, 2014;Yong et al, 2014).…”
Section: Confirmatory Factor Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…We choose employee innovative behavior as an outcome variable because, as innovation has been widely regarded as an important source of an organization's competitive advantage, it is essential to identify factors that increase team innovation performance (Shin et al, 2017). Scholars have increasingly suggested that conflict is an important perspective for studies on innovation (Hu et al, 2017). Previous studies on how conflict affected team innovation generated mixed results: some indicated that cognitive conflict could promote team innovation (Lu et al, 2011), whereas others proposed that both cognitive and affective conflicts negatively related to innovation (He et al, 2014;Yong et al, 2014).…”
Section: Confirmatory Factor Analysismentioning
confidence: 99%
“…Previous studies on how conflict affected team innovation generated mixed results: some indicated that cognitive conflict could promote team innovation (Lu et al, 2011), whereas others proposed that both cognitive and affective conflicts negatively related to innovation (He et al, 2014;Yong et al, 2014). To explain the inconsistent relationship between conflicts and innovation, researchers tried to investigate important moderators (He et al, 2014;Hu et al, 2017), but studies on the effects of the structural nature of conflict remain scant. We suggest that some of this inconsistency may be due to the unobserved conflict dimensions, interest-based conflict and behavioral conflict, which could affect team innovation performance as well.…”
Section: Confirmatory Factor Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Di lain pihak, walaupun sudah lebih dari 70 tahun penelitian tentang konflik dalam bidang psikologi telah dilaksanakan (Brørby, 2013), pada saat ini penelitian dalam bidang ini masih terbatas pada topik-topik terkait kepemimpinan yang efektif dalam resolusi konflik antara kelompok budaya yang berbeda (Chrobot-Mason, Ruderman, Weber, Ohlott, & Dalton, 2007;Hu, Chen, Gu, Huang, & Liu, 2017), aspek budaya dari manajemen sumber daya manusia (Aza, 2017;Rodrigues & Sbragia, 2013), atau topik-topik kepemimpinan lintas budaya dalam hubungan dengan manajemen konflik (Grisham & Walker, 2008;Snaebjornsson, Edvardsson, Zydziunnaite, & Vaiman, 2015).…”
Section: Pendahuluanunclassified
“…Task conflicts are related to rational behaviour due to which it doesn't cause tense relationship between teams (Jehn & Bendersky, 2003). Task conflict is positively related to team performance due to which it can improve team performance but if the level of task conflict is very high it can become destructive for team performance (Chen et al, 2014;De Dreu & Weingart, 2003;Hu, Chen, Gu, Huang, & Liu, 2017) .Task oriented conflict can be catalyst for cooperation (Lee, Huh, & Reigeluth, 2015). Conflicts can occur during all stages of construction project.…”
Section: Task Conflictmentioning
confidence: 99%